Evaluate Bussines Study of Dairy Cattle on Financial Aspect at Dairy Cattle Farmers Partnership Project In Banyumas Regency - Aunurohman, H; Muatip, Krismiwati (ANIMAL PRODUCTION, 2004)
This research aimed to (1) evaluate feasibility business study on financial aspect dairy cattle farmers partnership government project in Banyumas Regency, (2) to study and to analyze farm management dairy cattle (cost and revenue) at the fifth year on business study dairy cattle. The study applied survey methode. Sample was collected in two step. The first step, determining location of study using purposive sampling technique. Four subregencies that accepted cows from government in 1998 were chosin as the location. The Second step determining responders of study using purposive sampling technique by collecting all breeders on the locations that accepted the government support in the form of cows in 1998. Result of this research indicated on breeders that accepted the support in form of one cows and two cows was assumed feasible as reflected by Net Present Value (NPV) > 0 ; Net Benefit Cost Ratio (Net B/C ratio) > 1 ; Internal Rate of Return (IRR) > I (Social discount rate). At the fifth year, revenue were in form of one cow Rp 6.456.000,00 and two cows Rp 10.545.000,00. Profit received as one cow Rp 2.997.160,00 and two cows Rp 5.418.700,00. (Animal Production 6(2): 76-85 (2004) Key Words: Feasibility study, Farmer income, Farmer profitability